Social Networks And Future Orientation Of Females Entrepreneurs In Malaysia: The Mediate Effect Of Innovation And The Moderate Effect Of Access To Loan - Jabbar Jaafar, Najlah; Mohsin Alwazni, Jaafar Sadeq (Opción, 2019)
Women entrepreneurship development through extending small loan with purpose of start-up new business has become a global concern to address soci- oeconomic development and women empowerment goals, especially in devel- oping countries. However, most of the past studies paid attention on poverty reduction and women social empowerment through microcredit, particularly on household decisions making rather than business performance. this study explores the effect of future orientation, social networks on women small busi- nesses’ performance and examine the mediating effect of innovation activi- ties between future orientation, social networks and small businesses’ perfor- mance as well as the moderate effect of access to loan between innovation and small business performance.Methodology , Based on the questionnaire gathered from 149 of women entrepreneurs who received loan from Aman- ah Ikhair Malaysia (AIM), and 178 of women entrepreneurs who have not accessed to AIM loan. Finding, Our finding reveal that: (a) small business performance is significantly affected by the level of future orientation and the degree of social capital (b) innovation has positive effect in small business per- formance and plays a mediate role between future orientation, social capital and small business performance; (c) access to loan influence business perfor- mance positively moderate the relationship between innovation and business performance. Our finding provides theoretical implications notably to women entrepreneurship Originality/value, The activities of innovation have recognized to play an effective role in business development and growth. Nevertheless, the in- novation literature in small business still scarcity, especially on women entrepreneurs. This study is one few studies investigated how the level of women social networks influences their innovation activities and business performance, and the first one that explores the effect of future on their innovation activities and businesses’ performance.